An icon of time: the verbal image of a holiday in Russian culture - Konnova M. (Слово.ру: балтийский акцент, 2013)
This article considers the temporal constants of the holiday of Christmas in I. S. Shmelev’s novel The Summer of the Lord. The key to understanding the verbal image of a holiday is the lines based on Christmas chants. An analysis of lexical and grammatical means of expressing temporal semantics shows that the past and the eternally present amalgamate in the description of a holiday: in the supra-temporal reality of a holiday, everything abides in the atemporal “now”.